2011
DOI: 10.1038/nn.2946
|View full text |Cite
|
Sign up to set email alerts
|

Central nervous system pericytes in health and disease

Abstract: Pericytes are uniquely positioned within the neurovascular unit to serve as vital integrators, coordinators and effectors of many neurovascular functions, including angiogenesis, blood-brain barrier (BBB) formation and maintenance, vascular stability and angioarchitecture, regulation of capillary blood flow and clearance of toxic cellular byproducts necessary for proper CNS homeostasis and neuronal function. New studies have revealed that pericyte deficiency in the CNS leads to BBB breakdown and brain hypoperf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
855
3
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 838 publications
(897 citation statements)
references
References 101 publications
19
855
3
3
Order By: Relevance
“…In the current study, Pdgfrb expression was also upregulated by chronic hypoperfusion in the BCAS mice. Given that the PDGFRB is important for proliferation and migration of pericytes 55, PDGFRB may be increased in pericytes at a certain point, as compensation for hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, Pdgfrb expression was also upregulated by chronic hypoperfusion in the BCAS mice. Given that the PDGFRB is important for proliferation and migration of pericytes 55, PDGFRB may be increased in pericytes at a certain point, as compensation for hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…This meant that we could not directly relate our pathological findings to antemortem hypoperfusive and cognitive status. In addition, the lack of comparison of the SVD cases with controls without neurodegenerative pathologies was another limitation considering that PDGFRB positive pericytes may also degenerate in some neurodegenerative diseases 46, 55, 56, 59. The third limitation is that a histopathological study using postmortem human brains does not always uncover the entire cell process that occurs in the ageing human brain.…”
Section: Discussionmentioning
confidence: 99%
“…9,25 Future longitudinal CSF and BBB imaging biomarkers studies in living human APOE4 and APOE3 carriers with no cognitive impairment and/or with mild cognitive impairment should continue interrogating the role of BBB breakdown in the pathogenesis of dementia because of AD and other causes, as well as the role of pericyte loss and the studied molecular biomarkers of BBB breakdown in the living human brain.…”
mentioning
confidence: 99%
“…The present pharmacological experiment using the selective PDGFR inhibitor STI571 largely diminished proliferation of endothelial cells in the NH of adult mice. The signaling of PDGFB and PDGFRB plays a crucial role in the interaction of pericytes with endothelial cells by controlling the migration and shape conversion of pericytes (Lindahl et al 1997, Fukushi et al 2004, Ribatti et al 2011, Winkler et al 2011. The PDGFR inhibitor STI571 has been shown to inhibit angiogenesis by preventing PDGFRB of pericytes (Bauman et al 2007, Rocha et al 2007.…”
Section: Significance Of Vegf Signalingmentioning
confidence: 99%
“…The deficiency of Vegfa or Vegfr2 genes appears to be lethal due to abnormal blood vessel development (Shalaby et al 1995, Carmeliet et al 1996. The signaling pathway of platelet-derived growth factor B (PDGFB) and PDGF receptor beta (PDGFRB) is responsible for the recruitment of pericytes to new-born endothelial cells and controls the migration and shape conversion of pericytes (Lindahl et al 1997, Fukushi et al 2004, Winkler et al 2011. It has been shown that the embryos of Pdgfb-or Pdgfrb-deficient mice continue to develop until embryonic days 16-19, but widespread hemorrhage and edema cause embryonic lethality before birth (Lindahl et al 1997).…”
Section: Introductionmentioning
confidence: 99%